2016
DOI: 10.1088/0022-3727/49/10/105105
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism and optimal conditions for preparation of high-quality vanadium oxide films by organic sol–gel for optoelectronic applications

Abstract: Although vanadium oxides (VO x ) are important functional materials for academic research and industrial applications, the reaction mechanism of VO x prepared by organic sol–gel remains unclear. In order to investigate this mechanism, VO x organic sols were reacted at different temperatures, by which various VO x thin films were prepared. The products we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…This suggests that the chemical reactions for VO x organic gels during annealing in atmosphere at high temperatures are different from those for pure VO x in the similar conditions. For pure VO x , more O atoms in air will chemically react with V, thus causing the formation of VO x with higher valence states of V. But if VO x organic gel is heated, the decomposition of the VO x organic gel leads to the creations of numerous reductive gases, such as CO, H, R • radicals, and so forth . Such reductive gases suppress the chemical reactions of O 2 in air with V, and thus lower valence states of V are formed, as in our cases.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…This suggests that the chemical reactions for VO x organic gels during annealing in atmosphere at high temperatures are different from those for pure VO x in the similar conditions. For pure VO x , more O atoms in air will chemically react with V, thus causing the formation of VO x with higher valence states of V. But if VO x organic gel is heated, the decomposition of the VO x organic gel leads to the creations of numerous reductive gases, such as CO, H, R • radicals, and so forth . Such reductive gases suppress the chemical reactions of O 2 in air with V, and thus lower valence states of V are formed, as in our cases.…”
Section: Resultssupporting
confidence: 52%
“…For pure VO x , more O atoms in air will chemically react with V, thus causing the formation of VO x with higher valence states of V. But if VO x organic gel is heated, the decomposition of the VO x organic gel leads to the creations of numerous reductive gases, such as CO, H, R • radicals, and so forth. 28 Such reductive gases suppress the chemical reactions of O 2 in air with V, and thus lower valence states of V are formed, as in our cases. Therefore, it was previously observed that annealing of VO x organic gel in atmosphere at higher temperature leads to the formation of VO x with lower valence states of V. 29 The XRD patterns of the VO x films annealed at different T (Figure 3) reveal transitions from VO x organic gels to amorphous VO x at low annealing T, and further to crystalline VO x at higher T, as observed by Livage.…”
Section: Acs Applied Nano Materialssupporting
confidence: 59%
See 2 more Smart Citations
“…The alkali metals, lithium, potassium and sodium, can also sustain very strong plasmon resonances [8] but are extremely chemically reactive. For all these reasons there has been interest in trying to identify new materials that could be used in plasmonic applications [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%